A burning love for lesbian literature - Grier, Barbara; Factor, Rhonda J. (Journal of Lesbian Studies, 2001)
Barbara Grier’s enjoyment of and commitment to lesbian literature have been guiding forces in her life. While working non-professional jobs for little pay, she managed to find money to buy the books she loved. Her enthusiasm led her to devote considerable time and energy to The Ladder while simultaneously working a full-time job. When The Ladder was no longer financially viable, she founded Naiad Press, and, for the first nine years of its existence, continued to hold a full-time job. In 1982, she became the first paid employee of Naiad, which enabled her to focus exclusively on her passions: writing, editing, and publishing lesbian literature.
Keywords: amériques; genre; identités LGBTQIA2+; militance; personnes lesbiennes; ressource en ligne; régions géographiques; thématiques; éditions; états-unis